Halal Supply Chain Management dalam Optimalisasi Penerapan Sertifikasi Halal UMKM - Bernadhetta Vivi Kristiana; Anita Indrasari; Ida Giyanti (Performa: Media Ilmiah Teknik Industri, 2020)
Halal Small and Medium Enterprises (SMEs) give quite a substantial contribution to the country's economic growth. Halal certification is given to guarantee the halalness of the product and it’s expected to increase the profit of SMEs. However, in reality, there is no significant difference between the profits of SMEs with halal-certified and without one. This study aims to formulate how to optimize halal certification in order to increase the profits of halal SMEs by analyzing halal supply chain management. The qualitative method by literature reviews is used in this research. This research result is a formulation to optimize the SMEs halal certification, which consists of top management commitment in implementing halal policies, continuity of raw material fulfillment, building network with raw material suppliers, training for employees, procurement of SOPs and clear financial records, also building a good network structure for the parties involved.